Pediatric early warning score versus a paediatric triage tool in the emergency department: A reliability study - Hanne Branes; Anne Lee Solevåg; Marianne Trygg Solberg (Wiley, 2021)
Abstract Aim In the paediatric emergency department (PED), it is important to correctly prioritize children for physician assessment. The pediatric early warning score (PEWS), although not a triage tool, is often used for PED triage. The scandinavian Rapid Emergency Triage and Treatment System‐pediatric (RETTS‐p) is a reliability tested triage tool. We aimed to compare PEWS and RETTS‐p in a Norwegian PED. Design A reliability study. Methods The PED nurse routinely did PEWS observations, while the principal investigator concomitantly made RETTS‐p observations. Inter‐tool agreement was calculated for the complete PEWS and RETTS‐p and for vital signs scores, disregarding the RETTS‐p emergency symptoms and signs (ESS). Results Rapid Emergency Triage and Treatment System‐pediatric assigned a higher urgency than PEWS. The inter‐tool agreement between PEWS and RETTS‐p was low (weighted kappa [95% confidence interval [CI] = 0.32 [0.24-0.40]]). Weighted kappa (95% CI) was 0.50 (0.41-0.59) for PEWS and RETTS‐p without ESS, indicating that PEWS is not equivalent to five‐level triage tools.